2009
DOI: 10.1111/j.1600-0846.2008.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

A multitechnique evaluation of topical corticosteroid treatment

Abstract: Similar dynamics of skin modification during corticosteroid treatment was observed with very different techniques. Moreover, the potential of RF ultrasound analysis and mechanical skin measurement for characterizing skin structural and functional impairments has been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…This method has previously been used in similar type studies (11)(12)(13). For obtaining skin data on the forearm, the distance between epicondylos medialis humerii and processus styleoideus radii was measured.…”
Section: Subjects and Designmentioning
confidence: 99%
“…This method has previously been used in similar type studies (11)(12)(13). For obtaining skin data on the forearm, the distance between epicondylos medialis humerii and processus styleoideus radii was measured.…”
Section: Subjects and Designmentioning
confidence: 99%
“…In the present study, the use of sonoelastography to meet the aforementioned need relies on the observation that steroid-induced dermal atrophy is associated with loss of dermal elasticity [37][38][39]. Josse et al [38] found a good correlation between skin mechanical properties and histological assessment in atrophic skin.…”
Section: Discussionmentioning
confidence: 95%
“…Josse et al [38] found a good correlation between skin mechanical properties and histological assessment in atrophic skin.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 The in vivo characterization of corticosteroid-induced skin modifications at both cellular and extracellular levels and the dynamical study of these effects (e.g., their appearance and disappearance) require the use of 3-D noninvasive imaging methods. Optical coherence tomography 5 and confocal microscopy 6 can reveal, for example, epidermis thinning or the reduced size of the keratinocytes. However, since they lack specificity, they cannot provide access to other modifications induced in the cells or the elastic and collagen fibers networks.…”
Section: Introductionmentioning
confidence: 99%